Several Fractional Differences and Their Applications to Discrete Maps - Wu, Guo-Cheng; Baleanu, Dumitru; Zeng, Sheng-Da (Journal of Applied Nonlinear Dynamics, 2026)
Several definitions of fractional differences are discussed. Their applications to fractional maps are compared. As an example, the logistic equation of integer order is discretized by these fractional difference methods. The comparative results show that the discrete fractional calculus is an efficient tool and the maps derived in this way have simpler forms but hold rich dynamical behaviors.